The semiotic dimension of contemporary pragmatics - Niu, Min; Dechsubha, Thawascha (Technium Social Sciences Journal, 2022)
Contemporary Pragmatics has the semiotic features from the respects of disciplinary naming, the means of development, and theoretical source to research object and method. It is not only an independent linguistics and language science, but also an interdisciplinary field and paradigm. This paper is to explore the semiotic features and dimensions of Pragmatics for tracing back the origin and the theoretical resources from semiotic perspective, and to define its research scope and clarify the connotation of its conception. As Semiotics has a triad dimension of semiosis, one of which is the “pragmatic dimension”. Therefore, contemporary pragmatics includes at least three semiotic dimensions: scientific semiotics, linguistic semiotics and social semiotics. The semiotic analysis of Pragmatics could be conducive to clarify and fix the semiotic and philosophical origin, definition, disciplinary connotation and meaning of Pragmatics, which is also theoretically helpful for clarifying the concepts for the study of philosophical pragmatism, pragmaticism, semiotics, semantics and syntax. Key Words: Semiotic, Pragmatics, Pragmaticism